Strengthening Families: Knowledge of Parenting and Child Development - David C. Diehl; Jessica N. Wente; Larry F. Forthun (EDIS, 2011)
The list of topics that parents need to master is almost endless, starting before birth and extending all the way to adulthood. Rather than trying to answer all of the questions parents might have, this 3-page fact sheet focuses on the ways in which parents can explore their own parenting and find information and solutions that work for them. Written by David C. Diehl, Jessica N. Wente, and Larry F. Forthun, and published by the UF Department of Family, Youth and Community Sciences, December 2011.